Development of the Corticothalamic Projections - Grant, Eleanor L.; Hoerder-Suabedissen, Anna; Molnar, Zoltan (Frontiers in Neuroscience, 2012)
In this review we discuss recent advances in the understanding of corticothalamic axon guidance; patterning of the early telencephalon, the sequence and choreography of the development of projections from subplate, layers 5 and 6. These cortical subpopulations display different axonal outgrowth kinetics and innervate distinct thalamic nuclei in a temporal pattern determined by cortical layer identity and subclass specificity. Guidance by molecular cues, structural cues and activity dependent mechanisms contribute to this development. There is a substantial rearrangement of the corticofugal connectivity outside the thalamus at the border of and within the reticular thalamic nucleus, a region that shares some of the characteristics of the cortical subplate during development. The early transient circuits are not well understood, nor the extent to which this developmental pattern may be driven by peripheral sensory activity. We hypothesise that transient circuits during embryonic and early postnatal development are critical in the matching of the cortical and thalamic representations and forming the cortical circuits in the mature brain.